Competency-based medical education, here next? / Mohammed Fauzi Abdul Rani and Sabariah Abdul Rahman. - Abdul Rani, Mohammed Fauzi; Abdul Rahman, Sabariah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Competency Based Medical Education or CBME has been around for decades, the concept was even visualised as early as in the 70s [1, 2] and it has become more prominent and widespread as more evidence and experience guide us in understanding the concept and implementation. CBME to medical educationists in Malaysia is quite new. In the context of medical training, the Malaysian Medical Council (MMC) defines what the attributes of a good doctor are. Customarily we are introduced to ten traits that cover affective, skill and cognitive domains and across multiphases of practice; personal, professional, transdisciplines and grades, and interaction with patients and their relatives [3]. The inculcation of these attributes manifests themselves through the curriculum of a medical school. The wisdom is when a medical school and its curriculum are accredited one can assume that these attributes will manifest in their product, the doctor, through a system of evaluation that consists of many assessment methods. Or expressed in another way, the formulation of a medical curriculum is shaped by the need to ensure medical graduates possess all these attributes. In practice this is done primarily through accreditation of a medical program, the MMC and Malaysian Qualifying Agency (MQA) validate and approve medical education for doctors in training.